Analysis Of The Effect Of Discounts, Cashback, And Free Shipping On Repurchase Intention Through Customer Satisfaction Among Shopee Consumers (A Case Study Of FEB UM Pontianak Students) - Tiara Meilinda; Muhammad Ebuziyya Alif Ramadhan (UNIVED Press, 2026)
This study aims to examine the effect of Price Discounts, Cashback, and Free Shipping on Shopee consumers’ Repurchase Intention, with Customer Satisfaction as a mediating variable. As a leading e-commerce platform in Indonesia, Shopee implements various promotional strategies to retain customer loyalty, particularly through price discounts, cashback offers, and free shipping. The research employs an associative approach with a purposive sampling technique. A total of 100 respondents participated in the study, consisting of active students from the Faculty of Economics and Business, Universitas Muhammadiyah Pontianak, who had made at least two purchases on Shopee within the past year. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 3.0 software. The results show that all variables in the model meet the criteria for validity and reliability. The direct hypothesis testing reveals that Price Discounts, Cashback, and Free Shipping have a positive and significant effect on Customer Satisfaction. However, only Cashback and Free Shipping directly influence Repurchase Intention significantly. Furthermore, Customer Satisfaction has a positive and significant effect on Repurchase Intention. Indirect effect testing also indicates that Price Discounts, Cashback, and Free Shipping, when mediated by Customer Satisfaction, exert a positive and significant influence on Repurchase Intention.